The role of the Al-Abdari family in the flourishing of the scientific movement in Al-Andalus - Nawaf, Sura Mohammed; Nasief, Hamad Mohammed (Research Journal in Advanced Humanities, 2025)
This study presents an in-depth analysis of the role of the Abdari family as a distinguished model of the “scholarly families” that formed the foundation of Islamic civilization in Andalusia. The importance of this family is not limited to the individual contributions of its members; rather, it is evident in its institutional nature, which ensured the continuity of scientific production and the transmission of knowledge across successive generations. This contributed significantly to preserving the cultural and scientific fabric during periods of political turmoil. The family’s contributions were distinguished by their rare diversity and encompassed three main scientific fields: first, religious sciences, where its members excelled in Quranic recitations, exegesis, Prophetic hadith, and Maliki jurisprudence, and held positions of judge and fatwa issuer. second, the humanities, where they enriched the Arabic library with pioneering contributions in grammar, morphology, literature, poetry, and history, reflecting a profound awareness of the importance of language and the nation’s identity. Third, rational sciences, whose contributions extended to the fields of medicine, pharmacology, and arithmetic (mathematics), embodying the integration between traditional and rational sciences that characterized Islamic civilization at its peak. The study relied on the historical-analytical approach, tracing the biographies of family members in various historical and literary sources, enabling the development of a comprehensive picture of their collective role. It also analyzed the factors that ensured the continuity of this phenomenon, most notably: the early scientific education system within the family, the organic connection to educational institutions such as mosques and schools, the extensive network of relationships with scholars from the East and West, and the inheritance of academic and administrative positions. The study concludes that the Abdari family was not merely a nucleus of isolated scholars, but rather represented a comprehensive, micro-scientific institution that served as a fundamental cell in the body of Islamic civilization in Andalusia. This study not only provides a qualitative addition to the history of science in Andalusia, but also presents a rich historical model that can be used to understand the mechanisms of knowledge production, transmission, and sustainability in Islamic societies.